Guthrie test: pregnant women's perception during prenatal care - Silva,Maria Paula Custódio (2017)
Abstract Objectives: to investigate pregnant women's perception on Guthrie test and verify how this matter is approached during prenatal care. Methods: this study is an exploratory - descriptive, cross-sectional and quantitative approach design, carried out with 160 pregnant women who attended the Prenatal Care service at the Primary HealthCare in the city of Uberaba-MG. Data collection was performed between December 2014 and February 2015, using a semi-structured questionnaire. A bivariate descriptive statistics was applied by using the Pearson´s Chi-square test. Results: 75% of the pregnant women could not report which pathologies were to be screened, 16.3% reported that the diseases detected by Guthrie test had etiology genetic, 82% mentioned it was necessary to have more information on Guthrie test, 60% referred the necessity on focusing which diseases to be diagnosed. Only 36% of the pregnant women indicated the correct period (3rd to 7th day of the newborn life) for exam collecting. An average of 50% of the participants did not know about this prenatal test. Conclusions: pregnant women showed a low understanding regarding the test; there was a lack of understanding about prenatal matters. The nursing personnel play an important role in this stage to demonstrate their abilities in health education.